IMPROVEMENT OF CRIMINAL RESPONSIBILITY FOR BRIBERY IN LAW ENFORCEMENT PRACTICE OF THE REPUBLIC OF UZBEKISTAN - Bekzodjon Rustamov Dilmurodjon ugli (Journals Park Publishing, 2023)
This article discusses the problem of improving criminal liability for bribery in the law enforcement practice of the Republic of Uzbekistan. The introductory section provides an overview of the existing legislation and the main problems related to the fight against bribery. The methods section analyzes scientific research, as well as foreign experience in this field. The results section suggests specific measures to improve criminal liability for bribery. The discussion section analyzes the possible problems and advantages of the proposed measures. The conclusion contains the main conclusions and suggestions for improving law enforcement practice in the Republic of Uzbekistan.
Keywords: criminal liability, bribery, law enforcement practice, legislation, measures, struggle.